Coherent mapping of atrial tachycardias in patients with congenital heart disease. Issue 4 (16th February 2023) - Klehs, Sophia; Paech, Christian; Bertagnolli, Livio; Markel, Franziska; Dähnert, Ingo; Gebauer, Roman
Abstract: Aims: Coherent mapping (CM) uses a new algorithm to identify critical conduction isthmuses of atrial tachycardias (ATs). We analysed our experience of ablation of AT in patients with congenital heart disease (CHD) with this new technology. Methods and results: All patients with CHD who had CM of AT using the high-density mapping PENTARAY™ catheter and three-dimensional electroanatomic mapping system Carto3 between June 2019 and June 2021 were included retrospectively ( n = 27). As a control group, 27 patients with CHD and mapping of AT without CM between March 2016 and June 2019 were included. In total, 54 ablation procedures were performed in 42 patients [median age 35 (interquartile range, IQR 30–48) years] and 64 ATs were induced and mapped (thereof 50 AT intraatrial re-entrant tachycardia and 14 AT ectopic AT). The median procedure duration was 180 (120–214) min and median fluoroscopy time was 10 (5.2–14) min. Acute success was 100% (27/27) in the Coherence group and 74% (20/27) in the non-Coherence group ( P = 0.01). During follow-up [median 26 (12–45) months], AT recurred in 28/54 patients, thereof 15 patients needed a re-ablation procedure. Log-rank test showed no difference in recurrence rate between the two groups ( P = 0.29). Three minor complications occurred (5.5%). Conclusion: Mapping of AT in patients with CHD using the PENTARAY™ mapping catheter and the CM algorithm led to excellent acute success. All ATs were possible to map and no complications related to the PENTARAY™ mapping catheter were observed. Thus, the use of the CM algorithm represents a promising tool in patients with CHD and complex AT. Graphical Abstract: Graphical Abstract